Integrasi Pengembangan Kemampuan Kognitif, Afektif, dan Psikomotorik di Pesantren - Fajar Indarsih (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
the students in pesantren are not only taught religious knowledge, but how the practice of religious science can also be reflected in the attitudes and behaviors of students in their daily activities. The system in pesantren seeks to synergize between cognitive, affective, and psychomotor abilities. The method used is a qualitative research method, with a type of library approach. The data retrieval method uses documentation, and data analysis uses content or content analysis. Based on the results of the study and analysis, it can be formulated that Pesantren is an Islamic educational institution in Indonesia that is able to integrate cognitive, affective, and psychomotor abilities through systems. Among the development of cognitive abilities taught in Pesantren is moral science, in addition to the form of lessons, a rule is also regulated that forces students to practice the rules of pesantren which is a squeeze of the values of religious science.